Transcript of World Bank Group President David Malpass’s Interview with James Coomarasamy on BBC Radio’s The World Tonight - Malpass, David (World Bank, Washington, DC, 2022)
These remarks were delivered by the World Bank Group President David Malpass’s at the interview with James Coomarasamy on BBC Radio’s The World Tonight on May 19, 2022. He said that the key thing for the world is to create more supplies of energy of food of fertilizer, and move forward. He mentioned about lot of pressure on debt in developing countries because the contracts weren't transparent. He mentioned that there was Coronavirus (COVID-19) itself, the pandemic and the deaths but then also the shutdowns and in particular the shutdowns and closures of schools, and it is going to take years and years to make up for the educational losses that went on. He highlighted the course of inflation depends a lot on the amounts that can be added into the global economy to make up for some of the losses. He spoke about export bans are a big problem. He concluded by saying that it’s vital to end the war in Ukraine, and if that can't be done, then it's vital that countries around the world, and especially the advanced economies, announce new supplies of energy, of food and of fertilizer.